Aids in Infants and Children - Sunarto Sunarto (Indonesian Pediatric Society, 1992)
Children are infected by HIV, 80% vertically, from HIV infected mothetS mostly near or at delivery. Because heterosexual transmission of HIV among adults is more and more important it is estimated that at the end of this century there will be totally more than 10 million HIV infected children. Three quarters of HIV-infected babies show non specific symptoms at the early phase, including failure to thrive, chronic diarrhea, recurrent bacterial injections, mucocutanous infection. Cytotropism of HIV to neroe cells resul.ts tn inflammation, neroe cell damage and neuronal loss. Progressive neurologic abnormalities and developmental milestone regression or developmental retardation will be the results. Pneumocystics carinii infection has worse prognosis than lymphocytic interstitial pneumonia which more commonly occurred in HIV injected children. Diarrhea is a troublesome problem in children with AIDS. Kaposi's sarcoma and secondary cancer are rare in pediatric AIDS. Anemia and thrombocytopenia is common among AIDS children. In developing countries children with AIDS die within the year following the appearance of the symptoms, whereas asymptomatic HIV-injected children will live longer with high risk of recurrent and opportunistic injections. The hallmark of AIDS in children is the same as in adults,iI.e. the decrease of the number and function of CD4 lymphocytes. This in turn influences the junctions of other immunocompetent cells and loss of immunity is the result. Many things are still unexplainable in children AIDS.